Symboliczne wymiary tajwańskiego nacjonalizmu (Politeja, 2023)
THE SYMBOLIC DIMENSION OF TAIWANESE NATIONALISMA great majority of Taiwanese people declare themselves to be Taiwanese only (61% in 2022) or Taiwanese and also Chinese (additional 31%), which gives an impression of ethnic and national unity. However, the divisive factors of (sub) ethnic grouping, language diversity and historical consciousness are still present. Taiwanese nationalism, which in its civilian form is organized around present state of Republic of China (ROC) as opposed to the People’s Republic of China (PRC). However, ROC, although de facto an independent state is not de iure a Taiwanese state, as can be seen in its national symbolism. The paper analyses this enthosymbolical dimension of Taiwanese national identity, discussing four main symbolical spheres: the memory of the 2-28 Incident; memory and idealization of the Japanese colonial period; strong presence of local languages, used alongside the official northern mandarin standard; and finally, the presence of the Aborigine people and their cultures. All these spheres are important in Taiwan symbolical space, and their importance is further strengthened by the actions of the state (public commemorations, protecting the cultural relicts of Japanese period, removing the ones connected with authoritarian regime of Chiang Kai shek etc.). However, the author remains doubtful if they have enough emotional and symbolical power to unite Taiwanese in the face of the Chinese threat. Closely related question is the future effect of the recommendations of the report of the Commision of Transitional Justice about the monuments of the KMT period, whose fate is a strongly contested issue, and which needs further research.